Marine-derived pipeline anticancer natural products: a review of their pharmacotherapeutic potential and molecular mechanisms - Mohamed Ali Seyed; Siddiqua Ayesha (SpringerOpen, 2021)
Abstract Background Cancer is a complex and most widespread disease and its prevalence is increasing worldwide, more in countries that are witnessing urbanization and rapid industrialization changes. Although tremendous progress has been made, the interest in targeting cancer has grown rapidly every year. This review underscores the importance of preventive and therapeutic strategies. Main text Natural products (NPs) from various sources including plants have always played a crucial role in cancer treatment. In this growing list, numerous unique secondary metabolites from marine sources have added and gaining attention and became potential players in drug discovery and development for various biomedical applications. Many NPs found in nature that normally contain both pharmacological and biological activity employed in pharmaceutical industry predominantly in anticancer pharmaceuticals because of their enormous range of structure entities with unique functional groups that attract and inspire for the creation of several new drug leads through synthetic chemistry. Although terrestrial medicinal plants have been the focus for the development of NPs, however, in the last three decades, marine origins that include invertebrates, plants, algae, and bacteria have unearthed numerous novel pharmaceutical compounds, generally referred as marine NPs and are evolving continuously as discipline in the molecular targeted drug discovery with the inclusion of advanced screening tools which revolutionized and became the component of antitumor modern research. Conclusions This comprehensive review summarizes some important and interesting pipeline marine NPs such as Salinosporamide A, Dolastatin derivatives, Aplidine/plitidepsin (Aplidin®) and Coibamide A, their anticancer properties and describes their mechanisms of action (MoA) with their efficacy and clinical potential as they have attracted interest for potential use in the treatment of various types of cancers.